2022
DOI: 10.1177/10600280211073009
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Use in Ischemic Stroke

Abstract: Objective: A literature review of antiplatelet agents for primary and secondary stroke prevention, including mechanism of action, cost, and reasons for lack of benefit. Data sources: Articles were gathered from MEDLINE, Cochrane Reviews, and PubMed databases (1980-2021). Abstracts from scientific meetings were considered. Search terms included ischemic stroke, aspirin, clopidogrel, dipyridamole, ticagrelor, cilostazol, prasugrel, glycoprotein IIb/IIIa inhibitors. Study selection and data extraction: English-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 203 publications
0
22
0
2
Order By: Relevance
“…We thank our colleagues for their response to our review article of antiplatelet use in ischemic stroke. 1 We agree with their discussion of the evidence behind dual antiplatelet therapy (DAPT) in intracranial atherosclerotic disease (ICAD), as well as the caveats in this under-researched subtype of stroke. 2 Recommendations for up to 90 days of DAPT in severe cases of ICAD (70%-99% stenosis) with low risk of haemorrhagic transformation have also been echoed by a recent systematic review (Level B evidence).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…We thank our colleagues for their response to our review article of antiplatelet use in ischemic stroke. 1 We agree with their discussion of the evidence behind dual antiplatelet therapy (DAPT) in intracranial atherosclerotic disease (ICAD), as well as the caveats in this under-researched subtype of stroke. 2 Recommendations for up to 90 days of DAPT in severe cases of ICAD (70%-99% stenosis) with low risk of haemorrhagic transformation have also been echoed by a recent systematic review (Level B evidence).…”
mentioning
confidence: 53%
“…ICAD is a condition with large potential for further research, and would benefit from randomized control trials investigating single versus dual antiplatelet therapy, choice of antiplatelet or antithrombotic agent (with consideration of genetic polymorphisms previously discussed in the review), 1 length of treatment, endovascular treatments, and novel therapies such as ischemic preconditioning. 11 The role that racial background may play on ICAD and its response to particular therapies should also be considered in these trials.…”
mentioning
confidence: 99%
“…Many experimental and clinical studies have shown that platelet aggregation mediated thrombosis was the main cause of ischemic stroke, which could lead to irreversible ischemic and hypoxic necrosis of brain tissue. Therefore, antithrombotic is well recognized to be the preferred strategy for the treatment of ischemic stroke [2,3] . Currently, the clinically used antithrombotic drugs can be divided into anticoagulants, thrombolytics and antiplatelet aggregation drugs according to the mechanisms of action, but all of them existed a certain degree of defects and side effects in their application, such as narrow therapeutic window, high bleeding risk, increased drug resistance, etc [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, antithrombotic is well recognized to be the preferred strategy for the treatment of ischemic stroke. [2,3] Currently, the clinically used antithrombotic drugs can be divided into anticoagulants, thrombolytics and antiplatelet aggregation drugs according to the mechanisms of action, but all of them existed a certain degree of defects and side effects in their application, such as narrow therapeutic window, high bleeding risk, increased drug resistance, etc. [4] Thus, there is an urgent need to explore novel antithrombotic drugs with less side effects and better efficacy to protect patients from ischemic injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Kamarova et al 1 reviewed antiplatelet agents used in primary and secondary stroke prevention. In their analysis on dual antiplatelet therapy (DAPT) following an acute ischemic stroke, the authors concluded that DAPT for up to 21 days reduced recurrent ischemic strokes in patients with minor stroke or high-risk transient ischemic attack (TIA) according to the CHANCE and POINT clinical trials.…”
mentioning
confidence: 99%